UI/UX Desain Aplikasi Mobile Money Changer pada PT. Gemilang Artha Valindo dengan Metode Design Thinking - Made Suci Ariantini; Putu Gede Surya Cipta Nugraha; Kadek Aditama (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
PT Gemilang Artha Valindo or what can be called GAV Money Changer is a company engaged in foreign currency exchange services, there are several problems faced by GAV Money Changer for now one of them is about transactions that are only done with the cash system or pay on the spot, it makes the transaction process quite time consuming. With these problems need to design prototype UI / UX mobile-based GAV money changer application with the aim of accommodating the wishes of users and as a reference for future product development.  Prototype development using the Design Thinking method with the stages of Empatize, Define, Ideate, Prototype and Test. The tool used for prototyping is Figma. The testing phase uses a User Experience Questionnaire (UEQ) test with a total of 31 respondents, the results obtained can be seen from the Benchmark Data that the attractiveness scale results have an average value of 2.01 (Excellent), Clarity has an average value of 1.99 (Good), Efficiency has an average value of 1.89 (Excellent), Accuracy has an average value of 1.77 (Excellent), Stimulation has an average value of 1.90 (Excellent) and Novelty has an average value of 0.93 (Above Average).